2018
DOI: 10.5505/ktd.2018.93584
|View full text |Cite
|
Sign up to set email alerts
|

Moral Sensitivity in Nurses Providing Care to Psychiatric Patients: A cross-sectional study

Abstract: YÖNTEM ve GEREÇLER: Tanımlayıcı ve kesitsel tipteki bu araştırma, Nisan-Temmuz 2017 tarihleri arasında gerçekleştirilmiştir. Bu araştırmanın örneklemini, Türkiye'de Doğu Anadolu bölgesinde yer alan ve 3. basamak sağlık hizmeti veren bir ruh sağlığı hastanesi ve toplum ruh sağlığı Merkezi'nde çalışan 105 hemşire oluşturmuştur. Veriler Kişisel Bilgi Formu ve Ahlaki Duyarlılık Anketi (ADA) ile toplanmıştır. BULGULAR: Çalışmaya katılan hemşirelerin ahlaki duyarlılıklarının yüksek düzeyde olduğu saptanmıştır. Topla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
2
2
0
1
Order By: Relevance
“…For example, while the ethical sensitivity of nurses was low in a study conducted in Brazil, studies conducted in Iran and Türkiye revealed that nurses had high ethical sensitivity. 14,[22][23][24] In other studies conducted with nurses, it was shown that the ethical sensitivities of nurses were moderate similar to our results. 13,14,[25][26][27][28] Differences in ethical sensitivity levels in current studies may be due to the tool used for evaluation, geographical region, and cultural differences because it is claimed that cultural values play a crucial role in the development of ethical sensitivity among health care providers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, while the ethical sensitivity of nurses was low in a study conducted in Brazil, studies conducted in Iran and Türkiye revealed that nurses had high ethical sensitivity. 14,[22][23][24] In other studies conducted with nurses, it was shown that the ethical sensitivities of nurses were moderate similar to our results. 13,14,[25][26][27][28] Differences in ethical sensitivity levels in current studies may be due to the tool used for evaluation, geographical region, and cultural differences because it is claimed that cultural values play a crucial role in the development of ethical sensitivity among health care providers.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the studies supporting or not supporting our findings were reached. 15,22,23,26,28,32,33 The ethics education status of the midwives participating in our study caused significant differences in ethical sensitivity sub-dimensions. Interestingly, it was determined that the ethical sensitivities of the midwives who did not receive ethics education in terms of benefiting and implementation were higher than those who received ethics education.…”
Section: Discussionmentioning
confidence: 91%
“…Results of this study have shown that the participants had higher than intermediate MS scores. Our findings are consistent with the results reported from other studies that have investigated MS in nurses (Basar & Cilingir, 2019;Borhani et al, 2017;Evrim, 2018; Kahriman İlknur (2017); Yeşilçinar et al, 2020). In the current study, it was found that the participants had the lowest MS in the "conflict" subdimension.…”
Section: Stage 2: Relationship Between MD and Mssupporting
confidence: 93%
“…Ethical sensitivity is the professional aspect of moral sensitivity. 7 Moral sensitivity, on the other hand, is the ability to detect an ethical problem and to understand the ethical consequences of a decision made on behalf of the patient. 8 A high ethical sensitivity contributes to vocational professionalism as well as it directly affects the quality of the nursing care, which will be provided for the patients.…”
Section: Introductionmentioning
confidence: 99%